A methodological proposal of content analysis for non-fiction movies at film archives - Domínguez-Delgado, Rubén; López-Hernández, María-Ángeles (Revista General de Información y Documentación, 2017)
Film content analysis is a crucial archival task which has been forgotten in our country by film archives and the theorists in the field of moving image librarianship. While users can selectively retrieve moving images at the main Spanish TV archives, the satisfaction of this informative need is not possible at Spanish film archives, due in part to the lack of analytical proposals. To fill this void, we are sketching a film content analysis methodology, both globally and scene by scene, for non-fiction movies, as a result of collecting the different contributions by the Spanish theorists during the last decades. We are also applying the methodology to the documentary movie 200 Km. (Group Discusión 14, 2003) and valuing the usefulness and effectiveness of our method, according to the obtained results.